PENATALAKSANAAN FISIOTERAPI PADA KASUS BRONKOPNEUMONIA DENGAN MODALITAS INFRA RED DANCHEST PHYSIOTHERAPY DI RSUP SURAKARTA - Bakhtiar Wicaksono; Ade Irma Nahdliyyah (SINERGI : Jurnal Riset Ilmiah, 2026)
Bronchopneumonia is a respiratory tract infection characterized by inflammation of the bronchioles and alveoli, resulting in impaired ventilation and gas exchange. Clinical problems include muscle spasm, increased sputum production, decreased chest expansion, dyspnea, and reduced functional activity. Physiotherapy interventions such as Infrared (IR) and chest physiotherapy are commonly used to address these issues. This study used a descriptive analytic design with a case study approach conducted at Surakarta Central General Hospital. The subject was a patient diagnosed with bronchopneumonia. Data were collected through physiotherapy assessments, including muscle spasm by palpation, sputum by auscultation, chest expansion using the midline method, dyspnea using the Borg Scale, and functional activity using the Barthel Index. Interventions were administered over three therapy sessions. After three sessions, there was no change in muscle spasm, Sputum decreased, Chest expansion improved, Dyspnea decreased, and functional activity increased, Physiotherapy management using IR and chest physiotherapy can reduce clinical problems in bronchopneumonia patients, particularly in decreasing sputum, improving chest expansion, reducing dyspnea, and enhancing functional activity